A cloned polyoma DNA fragment representing the 5' half of the early gene region is oncogenic. - Chowdhury, K (1980)
The two polyoma DNA fragments generated by cleavage with BamHI and EcoRI were cloned in pBR322, and their oncogenic potential was tested in vivo and in vitro. Only recombinant plasmid DNA containing a polyoma DNA fragment which extends clockwise from 58 to 0 map units and include approximately the 5'-proximal half of the early gene region produced tumors in newborn hamsters and transformed rat embryo cells in tissue culture. Southern blotting analysis indicated that the entire 2.2-kilobase polyoma BamHI-EcoRI fragment was intact in both a tumor cell line and a cell line transformed in culture which we examined. The presence of polyoma middle and small T antigen in these lines was demonstrated by immunoprecipitation and tryptic peptide mapping. DNA from a recombinant plasmid containing a polyoma genome deleted between 90 and 4 map units failed to induce tumors or transform cells.